Cerium dioxide nanoparticles affect in vitro fertilization in mice. Issue 1 (2nd January 2016) - Preaubert, Lise; Courbiere, Blandine; Achard, Vincent; Tassistro, Virginie; Greco, Fanny; Orsiere, Thierry; Bottero, Jean-Yves; Rose, Jérome; Auffan, Mélanie; Perrin, Jeanne
Abstract: Due to their catalytic and oxidative properties, cerium dioxide nanoparticles (CeO2 NPs) are widely used as diesel additive or as promising therapy in cancerology; yet, scarce data are available on their toxicity, and none on their reproductive toxicity. We showed a significant decrease of fertilization rate, assessed on 1272 oocytes, during in vitro fertilization (IVF) carried out in culture medium containing CeO2 NP at very low concentration (0.01 mg.l −1 ). We also showed significant DNA damage induced in vitro by CeO2 NP on mouse spermatozoa and oocytes at 0.01 mg.l −1 using Comet assay. Transmission Electron Microscopy did not detect any nanoparticles in the IVF samples at 0.01 mg.l −1, but showed, at high concentration (100 mg.l −1 ), their endocytosis by the cumulus cells surrounding oocytes and their accumulation along spermatozoa plasma membranes and oocytes zona pellucida. We did not observe any nanoparticles in the cytoplasm of spermatozoa, oocytes or embryos. This study demonstrates for the first time the impact of CeO2 NP on in vitro fertilization, as well as their genotoxicity on mouse spermatozoa and oocytes, at low nanoparticle concentration exposure. Decreased fertilization rates may result from: (1) CeO2 NP's genotoxicity on gametes; (2) a mechanical effect, disrupting gamete interaction and (3) oxidative stress induced by CeO2 NP. These results add new and important insights with regard to the reproductive toxicity of nanomaterials requesting urgent evaluation, and support several publications on metal nanoparticles reprotoxicity. Our data highlight the need for in vivo studies after low-dose exposure.